Ethical Agility in Dance Rethinking Technique in British Contemporary Dance - Colin, Noyale; Seago, Catherine; Stamp, Kathryn (Taylor & Francis, 2024)
This edited collection examines the potential of dance training for developing socially engaged individuals capable of forging ethical human relations for an ever-changing world and in turn frames dance as a fundamental part of human experience. This volume draws together a range of critical voices to reflect the inclusive potential of dance. The contributions offer perspectives on contemporary dance training in Britain from dance educators, scholars, practitioners and artists. Through examining the politics, values and ethics of learning dance today, this book argues for the need of a re-assessment of the evolving practices in dance training and techniques. Key questions address how the concept of 'technique' and associated systems of training in dance could be redefined to enable the collaboration of skills and application of ideas necessary to twenty-first-century dance. The editors present these ideas in different modes of writing. This collection of essays, conversations and manifestos offers a way to explore, debate and grasp the shifting values of contemporary dance. Examining these values in the applied field of dance reveals a complex and contrasting range of ideas, encompassing broad themes including the relationships between individuality and collectivity, rigour and creativity, and virtuosity and inclusivity. This volume points to ethical techniques as providing a way of navigating these contrasting values in dance. It serves as an invaluable resource for academics as well as practitioners and students.